Exposure to Electronic Media, Smoking and Alcohol Drinking Among Guyanese Adults - Shao, Liming; Zhang, Ting; Chen, Yanyan; Ghose, Bishwajit; Ji, Lu (Frontiers in Public Health, 2022)
Abstract: Use of electronic media has been shown to be associated with tobacco and alcohol consumption behaviour among adult population. Currently, not much is known about the risk factors of tobacco and alcohol consumption in Guyana. The present study aimed to explore the association between exposure to electronic media and tobacco and alcohol consumption by adjusting for the sociodemographic correlates. Methods: Data were obtained from the sixth round of Guyana Multiple Indicator Cluster Survey (MICS 2019-20). Sample population were 2,208 men and 5,872 women aged between 15 and 49 years. Outcome variables were self-reported lifetime use of tobacco and alcohol, and the main explanatory variables were the use of electronic media such as internet, television and radio. Data were analysed using descriptive and multivariable regression analysis in Stata version 17. Results: Overall, 55.5% (95%CI=53.4, 57.6) men and 44.5% (95%CI=42.4, 46.6) women reported ever smoking tobacco, while the percentage of ever drinking alcohol was 34.2% (95%CI=32.9, 35.4) and 65.8% (95%CI=64.6, 67.1) among men and women respectively. Internet users had significantly higher odds of ever consuming tobacco and alcohol, however, the association was not uniform across the sociodemographic variables. For smoking, the positive association with internet use was observed for women only [OR=1.32, 95%CI=1.09,1.59], whereas, for alcohol consumption the association with internet use was significantly positive among both men [OR=1.82, 95%CI=1.58,2.09]and women [OR=1.84, 95%CI=1.22,2.70]. Men and women who ever tried alcohol drinking had [OR=4.64, 95%CI=3.16,6.82] and [OR=10.62, 95%CI=7.83,14.40] times higher odds of trying tobacco smoking. Conclusion: Current findings indicate over a quarter of the participants reported ever smoking tobacco and more than three-fifths ever drinking alcohol. Electronic media use, especially that of internet, is a strong predictor of tobacco and alcohol consumption among Guyanese adults. Results also revealed a strong interrelation between alcohol and tobacco smoking, and suggesting that strengthening the tobacco prevention programs may reduce the prevalence of alcohol drinking as well.